THE EFFECT OF EARLY MOBILIZATION ON UTERINE INVOLUTION AFTER CESAREAN SECTION - Ani Dwi Ningrum; Jasmawati ,; Lukman Nulhakim (Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2023)
The rate of births through cesarean section is 17.6% (Riskesdas, 2018). Uterine involution is the process of the uterus returning to its pre-pregnancy state in terms of both form and position. Early mobilization is a policy aimed at promptly guiding patients out of bed and encouraging them to walk as soon as possible. Failure to engage in early mobilization can result in an increase in body temperature due to inadequate uterine involution, preventing the removal of residual blood and leading to infections. The objective of this study is to determine the effect of early mobilization on uterine involution in patients after Cesarean Section at Kudungga Kutai Timur Regional General Hospital. This study employs a quasi-experimental research design in the form of a two-group posttest-only design to assess the impact of early mobilization on uterine involution after Cesarean Section at Kudungga Kutai Timur Regional General Hospital. The study includes a sample size of 10 respondents in the intervention group and 10 respondents in the control group. The consecutive sampling technique is used for sampling. Research instruments include observation sheets. The results of the Mann-Whitney test show a significance value of 0.008 (p<0.05), leading to the rejection of the null hypothesis (H0). It can be concluded that there is a difference in uterine involution after early mobilization in patients after Cesarean Section in the postpartum ward of Kudungga Regional General Hospital in 2023.